Interactive Augmented Reality (Ar)-Based Learning Cards For Lun Bawang Language - Chuah, Kee Man; Annavelle, Munga Dicky (2019)
The learning of Lun Bawang among the younger generation is deteriorating due to the lack of learning materials that spur their interest. In this project, a set of interactive augmented reality (AR)-based learning cards was produced. Each card contains interactive elements of Lun Bawang words for young learners to learn.